The Creative Labor of 2D-to-3D Conversion as a Reformatting Practice - Todd Kushigemachi (Media Industries)
In cinema and media studies, research on stereoscopic cinema has largely focused on aesthetic and phenomenological questions that position 3D as a distinct medium. However, an analysis of 3D cinema through the lens of production and media industry studies allows for new approaches to stereoscopy, often in ways that resist or complicate the very notion of medium specificity. This article closely examines the London-based 3D conversion company DNEG and its predecessors, Prime Focus World and Gener8. By focusing on the self-statements of DNEG professionals in publicity materials and original interviews, this article explores how these practitioners describe the creative labor of converting 2D movies into 3D. In addition to deepening our understanding of 3D cinema, the complexities of these practitioner discourses suggest how further research can critically engage with similarly adaptive textual practices of “reformatting,” such as the pan-and-scan of widescreen films and the colorization of black-and-white films. Ultimately, this article argues that a critical interrogation of industrial authorship claims opens up a space to conceptualize the reformatting of movies as an act of creative interpretation.